THE IMPACT OF THE JALLIANWALA BAGH MASSACRE ON GANDHI - McCutcheon, Richard (My University, 1989)
This thesis examines Gandhi's personal spiritual growth. It focuses on his growing understanding of the relationship between suffering and systemic violence. Personal spirituality is virtually identical with political life for Gandhi, and it is possible to look at the developing socio-political situation in India between the years 1915 and 1921 with an eye to understanding major spiritual changes in Gandhi's personal life. This thesis advances the idea that the Jallianwala Bagh Massacre, a crime perpetrated against innocent Indian civilians, had a major impact on Gandhi's understanding of suffering and violence--particularly systemic violence. The Massacre amounted to a spiritual and hence political watershed in Gandhi's life.
Keywords: Religion; Religion